Implementation of the Marketing Mix Strategy in Increasing Sales Volume at Three-Five Convenience Stores in Tangerang City - Siti Mariam; Fika Aryani (Graduate Program Magister Manajemen Pendidikan, 2023)
Marketing Mix is ​​a marketing strategy integrating several vital elements to achieve business success. This strategy involves 7P elements: Product, Price, Place, Promotion, People, Process, and Physical Evidence. This research explores the implementation of the Marketing Mix strategy at the Tiga Lima Convenience Store in Tangerang City, which is a profitable fashion business in the long term because the need for clothes never decreases. This study aims to analyze how the Marketing Mix strategy can increase sales volume in the store and create customer satisfaction. The research method used is qualitative research with a descriptive approach and inductive analysis. Data was collected through documentation and direct interviews with related parties. The results of this study are expected to provide a deeper understanding of implementing the Marketing Mix strategy in the context of fashion stores. These findings will provide insights for entrepreneurs in optimizing their marketing strategies so that they can achieve success in the clothing business.